A case of surgically treated peristomal pyoderma gangrenosum in a patient with rheumatoid arthritis - Khajehnoori, Masoomeh (J Surg Case Rep, 2016)
Peristomal pyoderma gangrenosum (PPG) is a rare subtype of pyoderma gangrenosum that is difficult to diagnose and treat. It is characterized by the rapid progression of painful necrotic ulcer surrounding an area of abdominal stoma. It is almost exclusively associated with inflammatory bowel disease even after bowel surgery and is associated with significant morbidity. Diagnosis of pyoderma gangrenosum is based on exclusion of other disorders replicating some of its clinical features and histopathological evidence. This is a case report of a 56-year-old lady with rheumatoid arthritis who presented with rapidly progressing abdominal ulcer 8 months after a Hartmanns procedure for perforated diverticulitis. The ulcer had formed a large cavity causing faecal filling in the dependent defect. The other causes of ulcer were excluded with negative histopathology, negative polymerase chain reaction for Mycobacterium ulcerans and negative acid fast bacillus (AFB) test. She was diagnosed with PPG which is routinely treated medically due to risk of setting off a second focus of pyoderma if surgically intervened. However due to increased risk of faecal peritonitis, it was decided to proceed with surgical debridement. This article will discuss the case in more detail and briefly discuss diagnosis and treatment options for PPG.